2020
DOI: 10.31449/inf.v44i1.2596
|View full text |Cite
|
Sign up to set email alerts
|

Feature Level Fusion of Face and voice Biometrics systems using Artificial Neural Network for personal recognition

Abstract: Lately, human recognition and identification has acquired much more attention than it had before, due to the fact that computer science nowadays is offering lots of alternatives to solve this problem, aiming to achieve the best security levels. One way is to fuse different modalities as face, voice, fingerprint and other biometric identifiers. The topics of computer vision and machine learning have recently become the state-of-the-art techniques when it comes to solving problems that involve huge amounts of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Comparative models have proven their performance in similar fields such as scene text recognition [21], dynamic gesture recognition [22], hyperspectral image classification [23], emotion recognition [24], event surveillance [25], traffic forecasting [26], air quality prediction [27], facial expression recognition [28], etc. These good results encourage us to explore the recognition, by comparable networks, of other biometric forms such as hand or earlobe morphology, retinal and iris physiognomy [29], voice [30,31], and signatures [32], especially those that have been forged or falsified or altered [33]. These biometric patterns play as crucial a role as fingerprints in forensic investigative procedures and in establishing proof of innocence or indictment.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative models have proven their performance in similar fields such as scene text recognition [21], dynamic gesture recognition [22], hyperspectral image classification [23], emotion recognition [24], event surveillance [25], traffic forecasting [26], air quality prediction [27], facial expression recognition [28], etc. These good results encourage us to explore the recognition, by comparable networks, of other biometric forms such as hand or earlobe morphology, retinal and iris physiognomy [29], voice [30,31], and signatures [32], especially those that have been forged or falsified or altered [33]. These biometric patterns play as crucial a role as fingerprints in forensic investigative procedures and in establishing proof of innocence or indictment.…”
Section: Resultsmentioning
confidence: 99%
“…ANN is characterized by a strong self-learning capability that enables the algorithm to achieve higher accuracy [12]. It has an extensive application in fields such as face recognition [13]. The algorithm first performs weighted summation on all the signals before processing the previous input, and the calculation formula is:…”
Section: Neural Network-based Recommendation Techniquementioning
confidence: 99%
“…Thus, matching score fusion achieved 0.62% equal error rate (EER), whereas feature fusion achieved 2.81% EER. In [29], a face-voice multimodal recognition approach was proposed and a number of experiments were conducted in three feature fusion mechanisms, concatenation of pre-normalized features, merging normalized features, and multiplication of features. The results showed that the merging fusion was the most effective mechanism.…”
Section: Face and Voice Fusionmentioning
confidence: 99%